ESG Concept as the Newest Determinant of Corporate Risk Management Strategies of Multinational Enterprises - Rushkovskyi, Mykhailo (International Journal Of Management And Economics Invention, 2022)
Within the rapid development of the world economy in recent decades, the growth of stable financing, including the increase in the number of relevant financial products, the attention of investors, politicians and various stakeholders in civil society has been drawn to the potential of multinational enterprises (MNE) to bring financial returns in accordance with social values and to make their contribution to overall macroeconomic stability and the fight against climate change. In particular, investing according to the concept of environmental, social and governance (ESG) has become a leading form of sustainable financing and has moved from early stages of development to mainstream financing in a number of leading countries. ESG ratings applied to MNE, which accounted for about 80% of the global economy's market capitalization in 2020, have evolved in recent years to incorporate long-term financial risks and opportunities into investment decision-making processes. An effective risk and opportunity management system, as well as appropriate risk management strategies, are an important component of the effective implementation of the ESG concept in the activities of MNE. A significant role is played by the risk management system of MNE in the areas of environmental factors (environmental) and the latest system of corporate governance (governance).